A proof of concept trial of the anti-EGFR antibody mixture Sym004 in patients with squamous cell carcinoma of the head and neck - Machiels, Jean-Pascal; Krauß, Jürgen (Cancer chemotherapy and pharmacology, 2015)
PurposeThe purpose of the trial was to assess the efficacy and tolerability of Sym004, a novel 1:1 mixture of two chimeric monoclonal antibodies (992 and 1024) targeting non-overlapping epitopes of the anti-epidermal growth factor receptor (EGFR), in patients with squamous cell carcinoma of the head and neck (SCCHN). MethodsIncurable, recurrent and/or metastatic SCCHN patients with acquired resistance to anti-EGFR monoclonal antibody-containing treatment received weekly infusions of 12 mg/kg Sym004 until disease progression or unacceptable toxicity.ResultsAmong the 26 patients treated with Sym004, the proportion of patients alive without disease progression at 6 months was 12 % (95 % CI 1-39 %). The median duration of progression-free survival was 82 days (95 % CI 41-140 days). Of 19 patients evaluable for response, eight showed a decrease in the sum of the largest diameter in their target lesions (median 11 %; range 7-27 %). The best overall response was stable disease in 13 patients (50 %). Paired biopsies showed a significant down-regulation of EGFR in both skin and tumors following exposure to Sym004. All patients had EGFR-related adverse events, including grade 3 skin toxicities and grade ≥3 hypomagnesemia reported in 13 (50 %) and 10 (38 %) of 26 patients, respectively. One event fulfilling the protocol-defined criteria for infusion-related reactions (grade 2) was reported. No anti-drug antibodies were detected.ConclusionsThe marked EGFR down-regulation shown in target tissues supports the proposed mechanism of action of Sym004. This trial revealed modest anti-tumor activity of Sym004 in extensively pretreated advanced SCCHN patients.